Electrochemical dealloying in ChCl-Urea Deep eutectic solvent: A strategy to fabricate porous FeCoNiAlMo high-entropy alloy with enhanced oxygen evolution reaction activity - Jiangfei Wang; Weijia Chen; Yijun Wen; Yuhan Peng; Siqi Liu; Shiwei He (Materials Letters: X)
High-entropy alloys (HEAs), as a new type of multi-element alloy, have become widely studied electrocatalytic materials in recent years due to their excellent catalytic performance. The experimental material used FeCoNiAlMo HEA with equal atomic ratio as the precursor, and three-dimensional nanostructures were formed by dealloying in choline chloride-urea (ChCl-Urea). The results indicate that Fe20Co20Ni20Al20Mo20 HEA is mainly composed of body-centered cubic (BCC) phase and face-centered cubic (FCC) phase, with BCC phase accounting for a larger proportion. Due to the different corrosion resistance of elements and the difference in element content distribution between the two phases, the FCC phase is preferentially corroded, resulting in a three-dimensional porous morphology. This unique structure synergistically reduces the energy barrier during the hydrolysis dissociation process, giving the material a significant advantage in the oxygen evolution reaction (OER) process. At a current density of 10 mA cm−2, the overpotential of the treated alloy is as low as 312 mV, which is lower than the commercial RuO2-IrO2, and it has lower resistance and higher charge transfer efficiency.